Wild boar under fire: the effect of spatial behaviour, habitat use and social class on hunting mortality. (25th May 2017) - Merli, E.; Grignolio, S.; Marcon, A.; Apollonio, M.
Abstract: The wild boar ( Sus scrofa ) is an ungulate of major management concern, often controlled only by indiscriminate, recreational hunting, which represents its main cause of death. Several studies have dealt with the effects of hunting on wild boar populations, pointing out controversial changes in spatial behavior and habitat use related to it. However, little information on the relationship between spatial behavior, habitat use and hunting mortality is available. In this study, 105 wild boars were monitored by means of radio‐tracking. Their cause of death was assessed, thus confirming the major role of hunting. For 89 of them, spatial behavior and habitat use as well as social class were related to hunting mortality. Spatial behavior, expressed as home range size, average daily distance among fixes and familiarity with the hunting area, resulted in having no strong effect on hunting mortality. Conversely, the relationship between the wild boar and the habitat, expressed in the proportion of forests in the home range, landscape complexity and habitat diversity, had a major role in predicting hunting mortality. In particular, the best model including social class and refuges pointed out a positive effect of landscape complexity on hunting mortality, while animals having a higher proportion of forests in their home range (assessed when this did not overlap the protected area) were less likely to be culled. Adult males and subadults of both sexes were more liable to be hunted than family groups. On the whole, behavioral and ecological differences in hunting vulnerability should be taken into account in management plans in order to optimize population management. Abstract : We investigated the cause of death of 105 wild boars monitored by means of radio‐tracking. For 89 of them, spatial behavior, habitat use and social class were related to hunting mortality. Spatial behavior did not significantly affect hunting mortality, which however was affected by the proportion of forests in the home range, landscape complexity and habitat diversity. Moreover, adult males and subadults of both sexes were more liable to be hunted than family groups. Accordingly, behavioral and ecological differences in hunting vulnerability should be taken into account in population management plans. Photo credit: Andrea Castellini.